2018
DOI: 10.3892/mmr.2018.8994
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin protects against inflammation, MMP‑2 activation and apoptosis induction in rat model of cardiopulmonary resuscitation through modulating Bmi‑1 expression

Abstract: With extensive pharmacological actions, quercetin has anti‑oxidant, free radical scavenging, anti‑tumor, anti‑inflammatory, anti‑bacterial and anti‑viral activity. Quercetin also reduces blood glucose and reduces high blood pressure, and has immunoregulation and cardiovascular protection functions. Additionally, it has been reported that it can reduce depression. The current study evaluated whether quercetin protects against inflammation, matrix metalloproteinase‑2 (MMP‑2) activation and apoptosis induction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Quercetin is a flavonoid that has proven to be effective in combating the production of reactive oxygen species and has positively modified the values of biochemical markers of homeostatic functions of organs and tissues (12)(13)(14)(15)(16)(17), including kidneys in different situations (11) such as warm ischemia (18)(19)(20). Our quantitative results corroborate that the use of quercetin is beneficial in warm renal ischemia.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Quercetin is a flavonoid that has proven to be effective in combating the production of reactive oxygen species and has positively modified the values of biochemical markers of homeostatic functions of organs and tissues (12)(13)(14)(15)(16)(17), including kidneys in different situations (11) such as warm ischemia (18)(19)(20). Our quantitative results corroborate that the use of quercetin is beneficial in warm renal ischemia.…”
Section: Discussionsupporting
confidence: 72%
“…Quercetin has shown positive results under different experimental conditions, mainly attributed to its antioxidant and anti-inflammatory properties (11)(12)(13)(14). This flavonoid has also been shown to be promising when associated with warm ischemia in different organs and tissues (15)(16)(17) and, more specifically, in the kidney (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, phenolic compounds have been shown to be effective agents in scavenging reactive species responsible for inducing oxidative stress. In concordance with chemical studies, quercetin was identified in the three extracts, which has been noted in the literature for its antioxidant activities [35,36], and anticancer [37], neuroprotection [38], hepatoprotection [39], anti-inflammatory [40], and antiparasitic [41,42] properties. Among the P. matricarioides extracts, higher antioxidant activity was observed in the PmC extract, which also displayed the higher concentration of quercetin according to the chemical profile as shown in the quantitative map.…”
Section: Discussionsupporting
confidence: 60%
“…There is also ample evidence that quercetin can reduce neuroinflammation and as previously indicated, the urolithin metabolic products derived from quercetin have more bioactivity than quercetin itself. In a rat cardiopulmonary resuscitation model of depression, quercetin inhibited ROS generation, neuroinflammation and metalloproteinase-2 protein expression corresponding to recovering left ventricular ejection fraction reduced by the depression paradigm (Wang D. et al, 2018). Mice undergoing chronic unpredictable stress for 21 days were simultaneously treated with 30 mg/kg of quercetin, which alleviated both anxiety and depression behavioral dysfunctions.…”
Section: Gut-brain-axis Mechanisms Linking Polyphenolic Microbial Metmentioning
confidence: 99%